Sistema hospedeiro-parasitoide associado à Piper glabratum Künth e P. mollicomum Künth (Piperaceae) no município de São Carlos, SP - Shimbori, Eduardo Mitio (2009)
This work presents biology and ecology data of host parasitoid insects associated with two plant species of the genus Piper L. (Piperaceae) ‐ P. glabratum and P. mollicomum. The phytophagous species studied belong to the order Lepidoptera and their parasitoids to the Hymenoptera and Diptera. The samples were carried out by entomological umbrella; the collected caterpillars were brought to the laboratory and reared. The 16 sampling points are distributed in eight fragments within the municipality of São Carlos. In each patch one Malaise trap was installed for collection of adult parasitoids. Through rearing, many host‐parasitoid associations were recorded, the majority unknown until the present. Results obtained for herbivorous and their parasitoids (richness, density and parasitism percentage) were explicit spatial and temporally. We also analyzed the food webs through quantitative parasitoid webs. Based on those results we discussed some of the relationships between the three trophic levels and analyzed some aspects of this system with environmental variables and landscape. Our results were dominated by high frequency of occurrence of only one host species ‐ Eois tegularia; we reared over a thousand parasitoids on this species. Hence we concluded the strong correlation between the number of species and the abundance of parasitoids and hosts. Comparisons between herbivores and parasitoids fauna on each species of host plant supported the hypothesis that host plant has a direct influence on the third trophic level. The herbivores were synchronous for points of collection; the data of frequency of occurrence were strongly autocorrelated in time. They also responded to the percentage of forest cover, which explains much of the variation in its richness.